In Vivo investigation of xenotransplanted human blood-derived scaffold into mice as a biodegradable construct for improvement of pelvic floor repair - Behnia-Willison, Fariba; Aryan, Pouria; Salehnia, Mojdeh; Willison, Nadia; Nguyen, Tran T. T.; Tansu, Nelson; Abbott, Derek (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveWe developed an autologous, novel human blood-derived scaffold (hBDS) to improve pelvic floor disorders. Both in vivo biocompatibility and biodegradation were investigated and compared by subcutaneous implantation, in the abdominal wall, and the back muscle of mice.Methods and MaterialsAfter preparing the scaffold, it was xenotransplanted subcutaneously, and in vivo biodegradation and host responses were assessed morphologically using hematoxylin, eosin, and Masson’s trichrome staining over 6 weeks. Immunohistochemistry for the CD136 marker was conducted to evaluate vascularization. In another series of experiments, the scaffold was sutured at multiple points on the abdominal wall and back muscle to prolong its biodegradation time and assess the scar formation around the transplantation site.ResultsThree days after implantation, no infection or severe inflammation was observed, and the scaffold was surrounded by connective tissue and fibroblasts, indicating initial scaffold degradation. By 1 week, the scaffold exhibited high biodegradation and increased fibroblast infiltration. Scaffold degradation was extensive at 2 weeks, with continued fibroblast infiltration and new collagen deposition. By 3 weeks, the scaffold had completely degraded, with minimal inflammation. The normal dermal structure was restored by weeks four to six after transplantation. Immunohistochemistry confirmed the neovascularization at one- and 2-week post- transplantation. Suturing the scaffold on the peritoneum and back muscle resulted in higher fibroblast infiltration and collagen formation around the suture compared to the non-suture group, with no morphological differences between the abdominal wall and back muscle reactions.ConclusionThe novel human blood-derived scaffold demonstrated biodegradation and high biocompatibility. Suturing the scaffold on the abdominal wall or back muscle effectively improves clinical symptoms, while further improvements are needed for its clinical application.